The effect of funding liquidity on financial stability in emerging markets: empirical analysis using system GMM estimation - Dahir, Ahmed Mohamed; Mahat, Fauziah (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
The purpose of this study is to examine the impact of funding liquidity and bank size on the financial stability for the period between 2006 and 2014 in BRIC countries. The study employs a system generalized method of moment (GMM) estimator and a sample of 53 publicly listed banks in BRIC. The results reveal that the funding liquidity and bank size are statistically significant and negative, which means higher funding liquidity, the fragility of the financial system increases more than 6 standard deviations. In addition, if the bank size increases by1, the risk of financial instability increases about 10%. The findings support the theory which argues large banks contribute to instability of banking system because complex banks have tendency to invest risky activities using short-term deposits. The interaction of bank size and funding liquidity is significant and positive suggesting that marginal effect of bank size on financial stability increases as the funding liquidity increases; however, bank’s activities are insignificant. This paper lends bank managers and regulatory agencies more insights about the sources of risk that may threaten the financial stability.